La regionalización sudamericana en el marco de la adopción e implementación de la Televisión Digital Terrestre - Calvache, María Belén (2016)
The document is a summary of the exploratory study on the efforts of South America (except Colombia) in the decision-making and implementation of the standard of Digital Terretrial Television(DTT), which was developed by Japan (1980) and modified by Brazil (2006). This one meets the geographic and demographic areas of Southern characteristics thatwill be the opportunity for Brazil to be the promoter of a common standard that benefits weither cultural ortechnological industries in the region.To determine the importance of a common decision and the reach of communication policies at regional level, the decision on implementation of standard analog television in the sixties and seventies in the continent andthe consequences derived from this process;in order to highlight the efforts of governments change in the communications landscape.